2021
DOI: 10.3390/jcm10225304
|View full text |Cite
|
Sign up to set email alerts
|

Posteroanterior Cervical Transcutaneous Spinal Cord Stimulation: Interactions with Cortical and Peripheral Nerve Stimulation

Abstract: Transcutaneous spinal cord stimulation (TSCS) has demonstrated potential to beneficially modulate spinal cord motor and autonomic circuitry. We are interested in pairing cervical TSCS with other forms of nervous system stimulation to enhance synaptic plasticity in circuits serving hand function. We use a novel configuration for cervical TSCS in which the anode is placed anteriorly over ~C4–C5 and the cathode posteriorly over ~T2–T4. We measured the effects of single pulses of TSCS paired with single pulses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Mixed activation of sensory posterior root and motor anterior root fibers would be disadvantageous for both major applications of transcutaneous spinal cord stimulation, i.e., neurophysiological and interventional studies. In neurophysiological studies, single-stimulus evoked PRM reflexes are utilized to probe the spinal sensorimotor circuits using specific conditioning-test paradigms [ 3 , 8 , 9 , 36 , 37 ]. The concomitant activation of anterior root efferents would lead to direct M wave-like responses superimposed on the EMG signals of the PRM reflexes, owing to their similar onset latencies [ 1 , 2 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mixed activation of sensory posterior root and motor anterior root fibers would be disadvantageous for both major applications of transcutaneous spinal cord stimulation, i.e., neurophysiological and interventional studies. In neurophysiological studies, single-stimulus evoked PRM reflexes are utilized to probe the spinal sensorimotor circuits using specific conditioning-test paradigms [ 3 , 8 , 9 , 36 , 37 ]. The concomitant activation of anterior root efferents would lead to direct M wave-like responses superimposed on the EMG signals of the PRM reflexes, owing to their similar onset latencies [ 1 , 2 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…After determining the stimulation site, the electrical stimulation was applied in bursts consisting of 10 rectangular biphasic pulses, with each lasting 100 µs. These bursts were delivered at a frequency of 30 Hz and accompanied by a carrier frequency of 10 kHz (as displayed in Figure 1C ) ( Wecht et al, 2021 ; McGeady et al, 2022b ). The stimulation current in the form of rectangular biphasic pulses helped to prevent net charge injection into the stimulated tissue by maintaining the charge balance, thereby reducing the risk of tissue damage ( Harnack et al, 2004 ; Hofmann et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…This difference based on functional demand is most clearly observed in the lower limbs, with contrasting effects in the Tibialis Anterior and Soleus motor pools when TMS is applied alone [28] or in combination with tSCS [29]. Recently, Wecht, Savage [30] demonstrated that subthreshold tSCS paired with synchronous TMS facilitates convergent transmission to upper-limb motor pools. Perhaps the longer latency (50 ms) potentiation observed in the current study-when the cathode was placed ipsilaterally-may, therefore, represent evidence of pre-synaptic cortico-motoneural excitation.…”
Section: Reflex Transmission Of Tscsmentioning
confidence: 99%